Preparation method of pre-dispersion liquid of core-shell particle modified epoxy resin
Through microemulsion polymerization and liquid-liquid phase transfer extraction technology, silicone rubber core-shell particle modified epoxy resin predispersion with an average particle size below 200 nm was prepared, which solved the nano-scale dispersion problem in the existing technology, achieved toughening and weathering improvement of epoxy resin, and was suitable for aerospace, electronic packaging and other fields.
Patent Information
- Application Number
- CN202510825402.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-08-12
AI Technical Summary
The prior art is difficult to efficiently prepare nano-scale uniformly dispersed silicone rubber core-shell particle modified epoxy resin, and the preparation process is complex, resulting in limited application in high-performance composite materials.
Silicone rubber cores below 100 nm were prepared by microemulsion polymerization, and the non-destructive dispersion of core-shell particles was achieved by regulating shell composition and liquid-liquid phase transfer extraction technology, and a core-shell particle-modified epoxy resin predispersion with an average particle size below 200 nm was prepared.
It realizes efficient and uniform dispersion of silicone rubber core-shell particles, maintains the thermodynamic properties of epoxy resin, provides good toughening effect and weather resistance, and is suitable for extreme environmental applications.
Smart Images

Figure CN120464137A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of organosilicon material synthesis and polymer material synthesis, and in particular to a method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin. Background Art
[0002] Epoxy resins are a class of thermosetting polymers containing epoxy groups. Their typical synthesis is through the polycondensation reaction of epichlorohydrin with polyols such as bisphenol A. As the core matrix resin for polymer-based composites, their performance advantages are multifaceted. The high reactivity of epoxy groups enables efficient crosslinking with amine and anhydride curing agents, forming a three-dimensional network structure. This imparts the material with exceptional mechanical properties (hardness exceeding Shore D80 and tensile strength exceeding 50 MPa) and low cure shrinkage (1%-2%), ensuring dimensional stability for precision components. In applications, they combine high-strength adhesion to metal and non-metal substrates (peel strength exceeding 10 kN / m), chemical resistance (withstanding pH 2-12 environments), and excellent electrical insulation. Consequently, they dominate the market for aerospace carbon fiber prepregs (composite materials account for over 60% of the market), microelectronics packaging (chip packaging market share exceeding 70%), and wear-resistant flooring for heavy machinery (wear resistance coefficient ≥ 0.6). However, due to its highly cross-linked structure, its inherent brittleness (elongation at break <5%) and limited thermal stability (glass transition temperature Tg is often below 200°C) have, to a certain extent, restricted its widespread application in high-tech fields. Therefore, research on toughening and high-temperature resistance modification of epoxy resins, as well as process performance optimization, has always been a focus of academic and industrial attention.
[0003] Epoxy resin toughening technology covers a variety of methods including liquid rubber, thermoplastic resin, nanoparticles, IPN, rigid particles and core-shell structures, each with its own characteristics: liquid rubber (such as CTBN) is low-cost but reduces strength and heat resistance; thermoplastic resin (such as PES) has good heat resistance but is difficult to process; nanoparticles (such as SiO2) have excellent overall performance but high dispersion cost; IPN process is complex; and rigid particles (such as glass beads) have limited toughening effect. In contrast, core-shell toughening (rubber core / PMMA shell) relies on the synergistic mechanism of the soft core efficiently absorbing impact (impact strength increased by 100-200%) and the hard shell strongly bonding with the matrix (modulus retention rate >85%). While significantly improving toughness and crack resistance, it maintains strength, heat resistance and processing performance. It is especially suitable for high-performance scenarios such as 5G high-frequency substrates, electronic packaging and aerospace load-bearing components (fatigue life increased by 3 times), and has become the current core solution for high-performance epoxy resins.
[0004] The rubber component of core-shell particles is typically composed of elastomers such as polybutadiene, polybutyl acrylate, and silicone rubber. Silicone rubber significantly outperforms polybutadiene and polybutyl acrylate in terms of temperature resistance, weatherability, chemical stability, mechanical properties, electrical insulation, and biocompatibility. It remains stable over a wide temperature range of -60°C to 250°C and exhibits excellent resistance to UV rays, acids, bases, and solvents, making it resistant to aging and degradation. Silicone rubber also exhibits high elasticity, low compression set, and excellent electrical insulation, making it suitable for use in harsh environments. In contrast, polybutadiene exhibits poor weatherability and high-temperature oxidation resistance, while polybutyl acrylate exhibits poor heat resistance, low mechanical strength, and sensitivity to certain solvents. Therefore, silicone rubber holds promise for broader and more reliable applications in aerospace, automotive, and electronics fields. The shell components of core-shell particles are typically polymethyl methacrylate and polystyrene, with relatively little research on other components. Therefore, adjusting the shell composition to refine and enhance its performance is a key area of research.
[0005] Currently, the performance of silicone core-shell modified epoxy resin products on the market is worse than that of polybutadiene rubber. The main reason is that the particle size of silicone core-shell products on the market is basically above 200nm, which is much larger than that of polybutadiene core-shell (100nm) products. Small particle size is more likely to cause microcracks and evenly disperse stress. Therefore, by reducing the particle size of the silicone core and adjusting the shell composition, it is expected to break through its toughening bottleneck while retaining the inherent high temperature resistance, weather resistance and biocompatibility advantages of silicone rubber, providing better solutions for extreme environment applications such as aerospace, electronic packaging, etc.
[0006] Microemulsion polymerization is a technique for preparing nanoscale polymer particles using a microemulsion system (droplet size 10-100 nm). It is characterized by high stability, small particle size distribution, and high monomer conversion. By adjusting the surfactant-to-monomer ratio, particle size can be precisely controlled. It is widely used in drug delivery, coatings, and functional nanomaterials. Mild reaction conditions produce excellent product properties.
[0007] Chinese patent application CN118931443 A reports an epoxy adhesive and its preparation method, wherein the toughening agent is prepared by emulsion polymerization using octamethylcyclotetrasiloxane and acrylate as monomers. Non-patent literature (Li Y, Zheng L, Peng S, Miao JT, Zhong J, Wu L, Weng Z. ACS Appl Mater Interfaces. 2020 Jan 29; 12 (4): 4917-4926.) reports a core-shell particle containing an epoxy group, the core of which is an organic silicone rubber and the exterior is an acrylate copolymer. However, these methods have the following characteristics: (1) The preparation process of the core-shell structured particles needs to undergo multiple post-processing steps such as demulsification, solid-liquid separation, centrifugal drying or freeze drying, which has the problem of complicated and tedious processes; (2) The material dispersion link needs to rely on strong mechanical forces such as high shear equipment or three-roll grinding. Even so, it is still difficult to avoid the core-shell particles from forming micron-sized agglomerates in the epoxy matrix. Therefore, the development of silicone rubber core-shell / epoxy pre-dispersion that can directly form nano-scale uniform dispersion (average particle size less than 200nm) without complex post-processing has become a technical bottleneck that urgently needs to be broken through in the current field of polymer composite materials. Summary of the Invention
[0008] In order to solve the problems of the prior art, the purpose of the present invention is to provide a method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin. This preparation method is to obtain a silicone rubber core less than 100nm by microemulsion polymerization, and then allow the silicone rubber core particle size to move freely below 200nm by regulating the subsequent amount of silicone monomers, and then use this as a seed to design its shell composition (glass transition temperature greater than 105°C), combine liquid-liquid phase transfer extraction technology to achieve basic losslessness of the core-shell particles, and then disperse them in epoxy resin, and remove most impurities, thereby streamlining and efficiently preparing a pre-dispersion liquid of core-shell particle modified epoxy resin, which has industrialization capabilities. The silicone core, the shell structure with a glass transition temperature greater than 105°C, the particle size less than 200nm, and the liquid-liquid phase transfer extraction and redispersion technology provide good high and low temperature performance, weather resistance, high toughness and good dispersion stability.
[0009] In order to achieve the above object, the technical solution adopted in the present invention is:
[0010] A method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin, comprising the following steps and conditions:
[0011] (1) 500 parts by weight of an organosilicon monomer, 1-100 parts by weight of a silane coupling agent, and 1-100 parts by weight of a double-bond silane coupling agent are uniformly mixed to obtain an organosilicon monomer mixed solution; 1-50 parts by weight of an acid or base catalyst and 1-500 parts by weight of deionized water are uniformly mixed to obtain an acid or base catalyst solution;
[0012] (2) by weight, 1-50 parts of emulsifier, 0-50 parts of co-emulsifier, 0-400 parts of deionized water and 1%-100% of the acid or base catalyst prepared in step (1) are mechanically stirred and heated to 20°C-90°C, 1%-100% of the organosilicon monomer mixture prepared in step (1) and 0%-99% of the acid or base catalyst are dropwise added within 1min-360min, the temperature is raised to 50°C-95°C, and the reaction is carried out for 5min-240min, the remaining organosilicon monomer mixture and acid or base catalyst are dropwise added within 0.5h-6h, the reaction is carried out at a constant temperature for 1h-6h, the temperature is lowered to 10-40°C, the pH is adjusted to 4-10 with an alkaline aqueous solution or an acidic aqueous solution, and the silicone rubber core emulsion is filtered;
[0013] (3) emulsifying 1-50 parts by weight of a double bond-containing monomer, 1-100 parts by weight of a hard monomer, 0.01-5 parts by weight of an emulsifier, and 3-100 parts by weight of deionized water using a high shear emulsifier for 1 minute to 10 minutes to obtain a double bond-containing pre-emulsion;
[0014] 1-25 parts of functional monomer, 1-50 parts of double bond-containing monomer, 1-100 parts of hard monomer, 0.01-5 parts of emulsifier, and 1-50 parts of deionized water are emulsified in a high shear emulsifier for 1 minute to 10 minutes to obtain a functional monomer emulsion;
[0015] 0-1 parts of buffer and 0-50 parts of deionized water are stirred and dissolved to obtain a buffer solution;
[0016] 0.01-5 parts of catalyst and 1-500 parts of deionized water are stirred and dissolved to obtain a catalyst solution;
[0017] (4) By weight, 100 parts of silicone rubber core emulsion, 0-5 parts of emulsifier, 0-50 parts of deionized water and the buffer solution prepared in step (3) are stirred and heated to 40-90° C., 1%-60% of the pre-emulsion containing double bonds and 1%-100% of the catalyst prepared in step (3) are added dropwise within 1 min-30 min, the temperature is raised to 50-90° C., the reaction is carried out for 1 min-120 min, the remaining pre-emulsion containing double bonds and 1%-99% of the catalyst prepared in step (3) are added dropwise within 0.5 h-4 h, the temperature is raised to 60-95° C., and the reaction is carried out for 0.5 h-6 h;
[0018] (5) cooling to 30-90° C., adding the functional monomer emulsion prepared in step (3) and the remaining catalyst solution dropwise within 1 min-120 min, heating to 50-95° C. and reacting for 0.5 h-6 h to prepare a silicone rubber core-shell emulsion;
[0019] (6) Add 20-400 parts of solvent by weight to the reaction kettle, start stirring at room temperature, and add 100 parts of silicone rubber core-shell emulsion dropwise within 1 minute to 60 minutes for extraction. Continue stirring for 1 minute to 30 minutes after the addition, and then stand for stratification for 0.5 hours to 24 hours, remove the lower aqueous layer, and obtain the upper silicone rubber core-shell particle solvent dispersion;
[0020] (7) 10-1000 parts by weight of the prepared silicone rubber core-shell particle solvent dispersion and 100 parts by weight of epoxy resin are added to a reaction kettle and stirred, and then the temperature is raised to 60-120° C. and the solvent is removed by vacuum distillation for 0.5 h to 5 h to prepare a pre-dispersion of core-shell particle modified epoxy resin.
[0021] Preferably, the organosilicon monomer in step (1) is one or a combination of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, octaphenylcyclotetrasiloxane, methylphenylcyclosiloxane, tetravinyltetramethylcyclotetrasiloxane, low molecular weight hydroxy silicone oil, etc.
[0022] Preferably, the silane coupling agent described in step (1) is methyltrimethoxysilane, methyltriethoxysilane, octyltriethoxysilane, phenyltrimethoxysilane, phenyltrimethoxysilane, tetraethyl silicate, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyl-trimethoxysilane, etc., or a combination thereof.
[0023] Preferably, the double bond-containing silane coupling agent in step (1) is one or a combination of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, etc.
[0024] Preferably, the acid catalyst in step (1) is one or a combination of benzenesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, formic acid, perchloric acid, etc. The base catalyst is one or a combination of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water, sodium oxide, potassium oxide, sodium methoxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide, tetramethylammonium hydroxide, etc.
[0025] Preferably, the emulsifier in steps (2) to (4) is one or a combination of sodium lauryl sulfate, sodium cetyl sulfate, sodium docusate, sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate, dodecylbenzenesulfonic acid, sodium didodecylphenyl ether disulfonate, fatty acid polyoxyethylene ester phosphate, sodium rosinate, sodium cyclohexane, sodium ricinoleate, isomeric tridecyl alcohol ether, polyoxyethylene octylphenol ether-10, sorbitan monolaurate, sorbitan monopalmitate, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyldimethylbenzyl ammonium chloride, etc.
[0026] Preferably, the co-emulsifier in step (2) is one or a combination of n-butanol, n-pentanol, ethylene glycol, ethanol, propylene glycol, isopropyl alcohol, polyvinyl alcohol, polyethylene glycol, acetone, butanone, ethyl acetate, methyl acetate, glycerol, polyglycerol ester, sodium chloride, sodium sulfate, sodium bicarbonate, etc.
[0027] Preferably, the alkaline aqueous solution in step (2) is one or a combination of ammonia water, sodium hydroxide aqueous solution, sodium bicarbonate aqueous solution, sodium formate aqueous solution, sodium acetate aqueous solution, ammonium acetate aqueous solution, disodium hydrogen phosphate aqueous solution, dipotassium hydrogen phosphate aqueous solution, sodium pyrophosphate aqueous solution, sodium phosphate aqueous solution, etc. The acidic aqueous solution is one or a combination of benzenesulfonic acid aqueous solution, p-toluenesulfonic acid aqueous solution, dodecylbenzenesulfonic acid aqueous solution, hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution, formic acid aqueous solution, perchloric acid aqueous solution, etc.
[0028] Preferably, the double bond-containing monomer in step (3) is one or a combination of styrene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, acrylic acid, lauryl methacrylate, glycidyl methacrylate, allyl glycidyl ether, allylamine, 4-vinylaniline, 4-penten-1-amine, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 1-penten-3-ol, acrylic acid, methacrylic acid, methylenesuccinic acid, maleic acid, crotonic acid, allyl methacrylate, divinylbenzene, dicyclopentadiene acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, ethoxypentaerythritol tetraacrylate, etc.
[0029] Preferably, the hard monomer described in step (3) is one or a combination of α-methylstyrene, N-vinylcarbazole, methacrylic acid, acrylamide, vinylnaphthalene, vinylimidazole, 3,4-ethylenedioxythiophene, maleimide, vinylbiphenyl, 4-vinylbenzoic acid, vinyltrimethoxysilane, 2-vinylpyridine, etc.
[0030] Preferably, the glass transition temperature of the ratio between the double bond pre-emulsion and the monomers in the functional monomer emulsion calculated by the FOX equation (Formula 1) is higher than 105°C.
[0031] 1 / T gn =W1 / T g1 +W2 / T g2 +···+W n / T gn (Formula 1)
[0032] T g1 : glass transition temperature of monomer 1;
[0033] T g2 : glass transition temperature of monomer 2;
[0034] T gn : glass transition temperature of monomer 3;
[0035] W1: mass proportion of monomer 1;
[0036] W2: mass proportion of monomer 2;
[0037] W n : Mass proportion of monomer 3.
[0038] Preferably, the functional monomer described in step (3) is one or a combination of epoxy-containing monomers (including but not limited to) glycidyl methacrylate and allyl glycidyl ether; amino-containing monomers (including but not limited to) allylamine, 4-vinylaniline, and 4-pentene-1-amine; hydroxyl-containing monomers (including but not limited to) hydroxyethyl methacrylate, hydroxypropyl methacrylate, and 1-pentene-3-ol; and carboxyl-containing monomers (including but not limited to) acrylic acid, methacrylic acid, methylenesuccinic acid, maleic acid, and crotonic acid.
[0039] Preferably, the buffering agent in step (3) is one or a combination of sodium bicarbonate, sodium formate, sodium acetate, ammonium acetate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium pyrophosphate, sodium phosphate, etc.
[0040] Preferably, the catalyst in step (3) is one or a combination of dicumyl peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, azobisisobutylonitrile initiator, azobisisoheptylonitrile, etc.
[0041] Preferably, the solvent in step (6) is one or a combination of methyl formate, ethyl acetate, vinyl acetate, cyclohexanone, acetone, butanone, methyl isobutyl ketone, ethanol, isopropanol, triethylene glycol, propylene glycol, diethanolamine, triethanolamine, cyclohexane, n-hexane, n-heptane, xylene, toluene, dimethylformamide, acetonitrile, N-methylpyrrolidone, ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol butyl ether, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, chloroform, dichloroethane, dichloromethane, etc.
[0042] Preferably, the epoxy resin described in step (7) is one or a combination of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, epoxidized olefin compound, heterocyclic and mixed epoxy resin, etc.
[0043] The pre-dispersion liquid of the present invention has epoxy resin as the continuous phase and core-shell particles as the dispersed phase. The core-shell particles have silicone rubber as the core and polyacrylate as the middle layer and the outermost layer. The glass transition temperature of the core is lower than 100°C, while the glass transition temperature of the middle layer and the outermost layer is higher than 105°C. The core-shell particles are prepared by emulsion polymerization, with an average particle size of less than 200nm, and the outermost layer has active functional groups such as amino, epoxy, hydroxyl, and carboxyl groups. The high cross-linking of epoxy resin leads to high brittleness. The modification of core-shell particles can achieve a good toughening effect. Since the core-shell structure does not cause a significant loss of thermodynamic properties, and the high glass transition temperature shell provides good force transmission, the thermodynamic properties are retained to the greatest extent, providing a better toughening effect. The dispersion problem of small-sized core-shell particles is solved by liquid-liquid extraction and then dispersed in epoxy resin, which has high dispersibility.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] 1. The present invention can prepare silicone rubber core-shell pre-dispersion liquid with a diameter below 200 nm, which can make up for the market deficiency and provide excellent performance.
[0046] 2. The present invention combines liquid-liquid phase transfer extraction technology, achieves essentially lossless redispersion, and efficiently prepares a pre-dispersion of core-shell particle-modified epoxy resin, which has industrialization capabilities.
[0047] 3. The present invention designs the composition of the middle layer and the outermost layer, with a high glass transition temperature and active functional groups, providing better force transmission and high temperature resistance, and high reactivity.
[0048] 4. While the present invention makes up for the deficiency of epoxy resin, the difference in refractive index between the core-shell particles and the matrix has a whitening effect, reduces the use of other auxiliary raw materials, and has good UV light transmittance and can be used for 3D printing. Description of the Drawings
[0049] Figure 1 It is the particle size distribution diagrams of the silicone rubber core emulsion (a), the active silicone rubber core-shell emulsion (b) and the epoxy resin pre-dispersion liquid (c) prepared in Example 1 of the present invention.
[0050] Figure 2 It is the SEM diagram of the cross section after curing of the epoxy resin pre-dispersion liquid added to the formula prepared in Example 1 of the present invention.
[0051] Figure 3 It is the model printed by a 355 nm 3D printer after adding the epoxy resin pre-dispersion liquid prepared in Example 1 of the present invention to the formula. Detailed Embodiments
[0052] In order to further explain the technical solution of the present invention, the present invention will be elaborated in detail through specific examples below.
[0053] The present invention is measured and evaluated according to the following methods.
[0054] 1. Solids Content
[0055] Weigh 2 g of the emulsion and place it in an oven at 120 °C for 1 h, or weigh 2 g of the dispersion liquid and place it in an oven at 100 °C for 0.5 h. Solids content = weight after drying g / 2 g × 100%.
[0056] 2. Average Particle Size and Polydispersity Index PDI of Rubber Particles and Core-Shell Particles
[0057] The average particle size and the polydispersity index PDI are measured by Zetasizer Nano ZS90. The emulsion is diluted with deionized water as the test sample, and the dispersion liquid is diluted with acetone as the test sample. The refractive index of the corresponding dispersion medium (water / acetone) and the refractive index of each rubber particle or core-shell particle are input for testing. PDI = 0 indicates that the particle system is completely monodisperse, that is, the sizes of all particles are exactly the same; PDI < 0.1 indicates that the system has a very narrow particle size distribution, and the particle sizes and the distribution are very uniform; 0.1 < PDI < 0.5 indicates that the particle size distribution is relatively uniform and the particle sizes are relatively consistent; PDI > 0.5 indicates that the particle size distribution in the system is relatively wide, there is a large degree of polydispersity, and the particle uniformity is poor; PDI > 1 usually means that the particle size distribution is very wide and the polydispersity is significant.
[0058] 3. Viscosity of Epoxy Resin Pre-dispersion Liquid
[0059] The viscosity of the epoxy resin pre-dispersion liquid is tested by a Brookfield RVDV2T rotational viscometer. The 27th rotor is selected to test the viscosity at 50 °C.
[0060] 4. The glass transition temperature is calculated by the above FOX equation (Formula 1). The following are the Tg values of some shell monomer homopolymers:
[0061]
[0062]
[0063] 5. Impact resistance (wedge impact method)
[0064] Symmetrical wedge test pieces were prepared according to the wedge method specified in GB / T 36877-2018, Adhesives - Determination of Impact Peel Strength. Tests were conducted at 25°C, -30°C, and -40°C with an impact velocity of 2 m / s and an impact energy of 50 J.
[0065] Example 1
[0066] (1) 100.0 g of octamethylcyclotetrasiloxane, 2.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 0.8 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0067] (2) 1.8 g of sodium dodecylbenzenesulfonate, 0.18 g of n-butanol, and 130.0 g of deionized water were added to a four-necked flask equipped with a constant temperature water bath and a reflux condenser and a mechanical stirrer. The temperature was raised to 50° C. with stirring, and 45% of the organic silicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The temperature was raised to 75° C. and the reaction was carried out for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 1.5 hours. The mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42%, the average particle size was 94.76 nm, and the PDI was 0.071.
[0068] (3) 0.25 g of sodium dodecylbenzenesulfonate, 12.5 g of deionized water, 23.5 g of α-methylstyrene, 1.0 g of acrylamide, and 0.54 g of butyl acrylate were added to a beaker in sequence, and emulsified for 2 min using a high shear emulsifier to obtain an α-methylstyrene pre-emulsion;
[0069] 0.2 g of sodium dodecylbenzenesulfonate, 1 g of deionized water, 0.4 g of methacrylic acid, 1.6 g of α-methylstyrene, and 0.03 g of styrene were added to a beaker in sequence and emulsified in a high shear emulsifier for 2 min to obtain a methacrylic acid emulsion.
[0070] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0071] Add 0.3 g of potassium persulfate and 45.0 g of deionized water into a beaker, and stir to mix evenly to obtain a catalytic solution.
[0072] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the α-methylstyrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining α-methylstyrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0073] (5) Cooling to 70°C, adding the methacrylic acid emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 minutes, heating to 85°C and reacting for 1 hour to prepare a silicone rubber core-shell emulsion with a solid content of 38%, an average particle size of 97.84 nm, a PDI of 0.029, and an outer shell T g =160℃.
[0074] (6) At room temperature, 200.0 g of ethyl acetate and 80.0 g of butanone were added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the emulsion was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain a transparent blue upper layer of silicone rubber core-shell ethyl acetate and butanone dispersion with a solid content of 29.6%.
[0075] (7) 84.5 g of silicone rubber core-shell ethyl acetate and butanone dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C with stirring and subjected to reduced pressure distillation for 1 h. The pre-dispersion of silicone rubber core-shell particles modified with epoxy resin (Z-1) was obtained. The core-shell content was 25%, the average particle size was 99.18 nm, the PDI was 0.058, and the viscosity was 3000 CP at 50°C.
[0076] See attached Figure 1 , which are particle size distribution diagrams of the pre-dispersed solutions of the silicone rubber core emulsion, silicone rubber core-shell emulsion, and silicone rubber core-shell particle-modified epoxy resin in Example 1 of the present invention. Figures (a), (b), and (c) correspond to the particle size distribution diagrams of the pre-dispersed solutions of the silicone rubber core emulsion, silicone rubber core-shell emulsion, and silicone rubber core-shell particle-modified epoxy resin, respectively. Their average particle sizes are less than 200 nm, and their PDIs are all less than 0.1, indicating that the systems have a very narrow particle size distribution and very uniform particle size and distribution.
[0077] See attached Figure 2This is an SEM image of a cross-section of the silicone rubber core-shell particle-modified epoxy resin pre-dispersion solution after curing in Example 1 of the present invention. The core-shell particles are uniformly distributed and have individual cavities, averaging approximately 100 nm, consistent with the particle size test results.
[0078] See attached Figure 3 This is a model printed using a 355nm 3D printer after adding the core-shell particle-modified epoxy resin pre-dispersion prepared in Example 1 of the present invention to the formula. The successful printing of the model indicates that it can be successfully used in 3D printing. The model is white, indicating that it has a whitening effect.
[0079] Example 2
[0080] (1) 100.0 g of octamethylcyclotetrasiloxane, 2.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 0.8 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0081] (2) 1.8 g of sodium dodecylbenzenesulfonate, 0.18 g of n-butanol, and 130.0 g of deionized water were added to a four-necked flask equipped with a constant temperature water bath and a reflux condenser and a mechanical stirrer. The temperature was raised to 50° C. with stirring, and 45% of the organic silicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The temperature was raised to 75° C. and the reaction was carried out for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 1.5 hours. The mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42%, the average particle size was 94.76 nm, and the PDI was 0.071.
[0082] (3) 0.25 g of sodium dodecylbenzenesulfonate, 12.5 g of deionized water, 22.9 g of α-methylstyrene, 1.0 g of acrylamide, and 1.1 g of butyl acrylate were added to a beaker in sequence and emulsified for 2 min using a high shear emulsifier to obtain an α-methylstyrene pre-emulsion;
[0083] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 0.4 g of methacrylic acid, 1.3 g of α-methylstyrene, and 0.3 g of styrene were added to a beaker in sequence and emulsified in a high shear emulsifier for 2 min to obtain a methacrylic acid emulsion;
[0084] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0085] Add 0.3 g of potassium persulfate and 45.0 g of deionized water into a beaker and stir to mix well to obtain a catalytic solution.
[0086] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the α-methylstyrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining α-methylstyrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0087] (5) Cooling to 70°C, adding the methacrylic acid emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 minutes, heating to 85°C and reacting for 1 hour to prepare a silicone rubber core-shell emulsion with a solid content of 38%, an average particle size of 97.66 nm, a PDI of 0.034, and an outer shell T g =150℃.
[0088] (6) At room temperature, 200.0 g of ethyl acetate and 80.0 g of butanone were added to the reactor, stirring was started, and 300 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain an upper transparent blue dispersion of ethyl acetate and butanone, which was the silicone rubber core-shell, with a solid content of 29.7%.
[0089] (7) 84.2 g of ethyl acetate and butanone dispersion of silicone rubber core-shell particles and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C with stirring and then distilled under reduced pressure for 1 h until no solvent was distilled out. The pre-dispersion of silicone rubber core-shell particles modified with epoxy resin (Z-2) was obtained. The core-shell content was 25%, the average particle size was 99.30 nm, the PDI was 0.045, and the viscosity was 2986 CP at 50°C.
[0090] Example 3
[0091] (1) 100.0 g of octamethylcyclotetrasiloxane, 2.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 0.8 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0092] (2) 1.8 g of sodium dodecylbenzenesulfonate, 0.18 g of n-butanol, and 130.0 g of deionized water were added to a four-necked flask equipped with a constant temperature water bath and a reflux condenser and a mechanical stirrer. The temperature was raised to 50° C. with stirring, and 45% of the organic silicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The temperature was raised to 75° C. and the reaction was carried out for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 1.5 hours. The mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42%, the average particle size was 94.76 nm, and the PDI was 0.071.
[0093] (3) 0.25 g of sodium dodecylbenzenesulfonate, 12.5 g of deionized water, 22.3 g of α-methylstyrene, 1.0 g of acrylamide, and 1.7 g of butyl acrylate were added to a beaker in sequence and emulsified for 2 min using a high shear emulsifier to obtain an α-methylstyrene pre-emulsion;
[0094] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 0.4 g of methacrylic acid, 1.0 g of α-methylstyrene, and 0.6 g of styrene were added to a beaker in sequence and emulsified in a high shear emulsifier for 2 min to obtain a methacrylic acid emulsion;
[0095] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0096] Add 0.3 g of potassium persulfate and 45.0 g of deionized water into a beaker, and stir to mix evenly to obtain a catalytic solution.
[0097] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the α-methylstyrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining α-methylstyrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0098] (5) Cooling to 70°C, adding the methacrylic acid emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 minutes, heating to 85°C and reacting for 1 hour to prepare a silicone rubber core-shell emulsion with a solid content of 38.0%, an average particle size of 97.80 nm, a PDI of 0.031, and an outer shell T g =140℃.
[0099] (6) At room temperature, 280.0 g of ethyl acetate was added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent blue silicone rubber core-shell dispersion with a solid content of 29.7%.
[0100] (7) 84.2 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C with stirring and distilled under reduced pressure for 1 h until no solvent was distilled out. The pre-dispersion of silicone rubber core-shell particles modified with epoxy resin (Z-3) was obtained. The core-shell content was 25%, the average particle size was 99.64 nm, the PDI was 0.047, and the viscosity was 2996 CP at 50°C.
[0101] Example 4
[0102] (1) 100.0 g of octamethylcyclotetrasiloxane, 2.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 0.8 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0103] (2) 1.8 g of sodium dodecylbenzenesulfonate, 0.18 g of n-butanol, and 130.0 g of deionized water were added to a four-necked flask equipped with a constant temperature water bath and a reflux condenser and a mechanical stirrer. The temperature was raised to 50° C. with stirring, and 45% of the organic silicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The temperature was raised to 75° C. and the reaction was carried out for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 1.5 hours. The mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42%, the average particle size was 94.76 nm, and the PDI was 0.071.
[0104] (3) 0.25 g of sodium dodecylbenzene sulfonate, 12.5 g of deionized water, 21.6 g of α-methylstyrene, 1.0 g of acrylamide, and 2.4 g of butyl acrylate were added to a beaker in sequence and emulsified for 2 min using a high shear emulsifier to obtain an α-methylstyrene pre-emulsion;
[0105] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 0.4 g of methacrylic acid, 0.8 g of α-methylstyrene, and 0.8 g of styrene were added to a beaker in sequence and emulsified in a high shear emulsifier for 2 min to obtain a methacrylic acid emulsion;
[0106] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0107] Add 0.4 g of potassium persulfate and 45.0 g of deionized water into a beaker, and stir to mix evenly to obtain a catalytic solution.
[0108] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the α-methylstyrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining α-methylstyrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0109] (5) Cooling to 70°C, adding the methacrylic acid emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 minutes, heating to 85°C and reacting for 1 hour to prepare a silicone rubber core-shell emulsion with a solid content of 38.5%, an average particle size of 97.71 nm, a PDI of 0.022, and an outer shell T g =130℃.
[0110] (6) At room temperature, 280.0 g of acetone was added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 4 h until the upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent blue silicone rubber core-shell dispersion with a solid content of 29.5%.
[0111] (7) 84.8 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C with stirring and then distilled under reduced pressure for 1 h without solvent removal to obtain a pre-dispersion of silicone rubber core-shell particles modified with epoxy resin (Z-4). The core-shell content was 25%, the average particle size was 99.57 nm, the PDI was 0.087, and the viscosity was 3005 CP at 50°C.
[0112] Example 5
[0113] (1) 100.0 g of octamethylcyclotetrasiloxane, 2.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 0.25 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0114] (2) 1.8 g of sodium dodecylbenzenesulfonate, 0.18 g of n-butanol, and 130.0 g of deionized water were added to a four-necked flask equipped with a constant temperature water bath and a reflux condenser and a mechanical stirrer. The temperature was raised to 50° C. with stirring, and 35% of the organic silicon monomer mixture and 35% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The temperature was raised to 75° C. and the reaction was carried out for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 2 hours. The reaction was carried out at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42.5%, the average particle size was 133.10 nm, and the PDI was 0.073.
[0115] (3) 0.25 g of sodium dodecylbenzenesulfonate, 12.5 g of deionized water, 23.5 g of α-methylstyrene, 1.0 g of acrylamide, and 0.5 g of butyl acrylate were added to a beaker in sequence and emulsified using a high shear emulsifier for 5 min to obtain an α-methylstyrene pre-emulsion;
[0116] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 0.4 g of methacrylic acid, and 1.6 g of α-methylstyrene were added to a beaker in sequence and emulsified using a high shear emulsifier for 6 min to obtain a methacrylic acid emulsion.
[0117] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0118] 0.27 g of potassium persulfate and 45.0 g of deionized water were added to a beaker, and the mixture was stirred and mixed to obtain a catalytic solution.
[0119] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 10.0 g of deionized water, 230.0 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the α-methylstyrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining α-methylstyrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0120] (5) Cooling to 70°C, adding the methacrylic acid emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 minutes, heating to 85°C and reacting for 1 hour to prepare a silicone rubber core-shell emulsion with a solid content of 37.5%, an average particle size of 136.91 nm, a PDI of 0.027, and an outer shell T g =160℃.
[0121] (6) At room temperature, 280 g of butanone was added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 10 min. Stirring was continued for 10 min after the addition was completed. Finally, the mixture was allowed to stand for 3 h until the upper and lower layers were completely separated. The lower layer was removed to obtain a transparent blue silicone rubber core-shell dispersion with a solid content of 29.6%.
[0122] (7) 84.5 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C with stirring and then distilled under reduced pressure for 1 h without solvent removal to obtain a small-size active silicone rubber core-shell particle pre-dispersion (Z-5) with a core-shell content of 25%, an average particle size of 139.24 nm, a PDI of 0.086, and a viscosity of 2500 CP at 50°C.
[0123] Example 6
[0124] (1) 100.0 g of octamethylcyclotetrasiloxane, 2.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 0.8 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0125] (2) 1.8 g of sodium dodecylbenzenesulfonate, 0.18 g of n-butanol, and 130.0 g of deionized water were added to a four-necked flask equipped with a constant temperature water bath and a reflux condenser and a mechanical stirrer. The temperature was raised to 50° C. with stirring, and 45% of the organic silicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The temperature was raised to 75° C. and the reaction was carried out for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 1.5 hours. The mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42.0%, the average particle size was 94.76 nm, and the PDI was 0.071.
[0126] (3) 0.25 g of sodium dodecylbenzenesulfonate, 12.5 g of deionized water, 21.6 g of α-methylstyrene, and 2.4 g of butyl acrylate were added to a beaker in sequence and emulsified using a high shear emulsifier for 5 min to obtain an α-methylstyrene pre-emulsion;
[0127] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 0.9 g of α-methylstyrene, and 1.1 g of styrene were added to a beaker in sequence and emulsified using a high shear emulsifier for 10 min to obtain a styrene emulsion;
[0128] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0129] 0.32 g of potassium persulfate and 45.0 g of deionized water were added to a beaker, and the mixture was stirred and mixed to obtain a catalytic solution.
[0130] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of the silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the α-methylstyrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining α-methylstyrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 4 hours.
[0131] (5) Cooling to 70°C, adding the amount of styrene emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 minutes, heating to 85°C and reacting for 1 hour to prepare a silicone rubber core-shell emulsion with a solid content of 38.2%, an average particle size of 97.79 nm, a PDI of 0.052, and an outer shell T g =130℃, no active functional groups.
[0132] (6) At room temperature, 200.0 g of ethyl acetate and 80.0 g of butanone were added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 4 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 4 h until the upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent blue silicone rubber core-shell dispersion with a solid content of 29.4%.
[0133] (7) 86.2 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C and distilled under reduced pressure for 1 h without solvent removal to obtain a small-size active silicone rubber core-shell particle pre-dispersion (Z-6). The core-shell content was 25%, the average particle size was 99.57 nm, the PDI was 0.087, and the viscosity was 3205 CP at 50°C.
[0134] The parameters of Examples 1-6 are summarized in Table 1.
[0135] Table 1
[0136]
[0137] Example 7
[0138] To 144.0 g of the pre-dispersion liquid (Z-1) of the silicone rubber core-shell particle modified epoxy resin prepared in Example 1 (core-shell ratio 25%), 8.0 g of glycidyl neodecanoate E-10P (Hansen HEXION E10P) as a reactive diluent, 8.0 g of dicyandiamide (Aladdin reagent, ≥99%) as a curing agent, 1.0 g of aromatic dimethyl urea (Azken accelerator DYHARD UR300) as a curing accelerator, 2.0 g of silica (Cabot white carbon black CAB-O-SIL TS720), 0.3 g of carbon black (Cabot MONARCH120 carbon black), 10.0 g of nano-calcium carbonate (Zhengzhou Yufeng Nanomaterial Co., Ltd.), and 5.0 g of calcium oxide (Aladdin reagent, reagent grade) were added. After mixing with a vacuum degassing mixer, the mixture was mixed and stirred three times with a three-roll mill to obtain an adhesive composition (S-1) containing core-shell particles. Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-1) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0139] Example 8
[0140] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the pre-dispersion liquid (Z-2) of silicone rubber core-shell particle modified epoxy resin. The remaining steps were the same as those in Example 7, and an adhesive composition (S-2) containing core-shell particles was obtained.
[0141] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-2) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0142] Example 9
[0143] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the pre-dispersion liquid (Z-3) of silicone rubber core-shell particle modified epoxy resin. The remaining steps were the same as those in Example 7, and an adhesive composition (S-3) containing core-shell particles was obtained.
[0144] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-3) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with the GB / T36877-2018 standard. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0145] Example 10
[0146] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the pre-dispersion liquid (Z-4) of silicone rubber core-shell particle modified epoxy resin. The remaining steps were the same as those in Example 7, and an adhesive composition (S-4) containing core-shell particles was obtained.
[0147] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-4) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with the GB / T36877-2018 standard. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0148] Example 11
[0149] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the pre-dispersion liquid (Z-5) of silicone rubber core-shell particle modified epoxy resin. The remaining steps were the same as those in Example 7, and an adhesive composition (S-5) containing core-shell particles was obtained.
[0150] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-5) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0151] Example 12
[0152] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the pre-dispersion liquid (Z-6) of silicone rubber core-shell particle modified epoxy resin. The remaining steps were the same as those in Example 7, and an adhesive composition (S-6) containing core-shell particles was obtained.
[0153] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-5) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0154] Comparative Example 1
[0155] To 90.0 g of KANE ACE MX-154 (bisphenol A epoxy resin: 60%, butadiene core-shell rubber particles: 40%, average particle size: 100 nm) was added bisphenol A epoxy resin (Nan Ya 128) to obtain an epoxy resin composition (Z-7, core-shell ratio 25%).
[0156] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the epoxy resin composition (Z-7). The remaining steps were the same as in Example 7, and an adhesive composition (S-7) containing core-shell particles was obtained.
[0157] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-7) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0158] Comparative Example 2
[0159] Product Name: KANE ACE MX-960 (bisphenol A epoxy resin: 60%, silicon core-shell rubber particles: 40%, average particle size: 300nm) Epoxy resin composition (Z-8, core-shell ratio 25%)
[0160] The pre-dispersion liquid (Z-1) of silicone rubber core-shell particle modified epoxy resin was replaced with the epoxy resin composition (Z-8). The remaining steps were the same as in Example 7, and an adhesive composition (S-8) containing core-shell particles was obtained.
[0161] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-8) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with the GB / T36877-2018 standard. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0162] The evaluation results of various physical properties of Examples 7-12 and Comparative Examples 1-2 are summarized in Table 2
[0163] Table 2
[0164]
[0165] 1. Silicone rubber particle size core: Examples 7-12, Comparative Example 2
[0166] As shown in Table 2, by comparing Example 7 with Example 11 and Comparative Example 2, it can be seen that as the particle size decreases, the impact resistance and adhesion are significantly improved regardless of room temperature or low temperature. Within the existing particle size range, the smaller the particle size, the better the toughening effect, and it is higher than the commercially available product in the comparative example.
[0167] 2. Comparison of silicone rubber core-shell and butadiene core-shell: Examples 7-12, Comparative Examples 1-2
[0168] As shown in Table 2, by comparing Examples 7-10 and Comparative Example 1, it can be seen that the particle sizes of the silicone rubber core-shell (Examples 7-10) and the polybutadiene core-shell (Comparative Example 1) are basically around 100 nm, but the impact resistance and adhesion of the silicone rubber core are significantly higher than that of the butadiene core.
[0169] 3. Comparison of the presence and absence of active functional groups: Example 10 and Example 12
[0170] As shown in Table 2, by comparing Example 10 with Example 12, it can be seen that the core particle size and T g Under the same conditions, the impact resistance and adhesion of the silicone core-shell with carboxyl groups are significantly higher than those without carboxyl groups, which shows that the functional group has a great influence.
[0171] 4. Comparison of glass transition temperature: Examples 7-10 and 12
[0172] As shown in Table 2, by comparing Examples 7-10 and 12, it can be seen that under the premise of the same core particle size and active functional groups, the impact resistance and adhesion increase with T g It can be seen that changing the shell composition can indeed affect its performance. g The increase can further promote the transmission of force.
Claims
1. A method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin, characterized in that: Here are the steps: (1) By weight, 500 parts of an organosilicon monomer, 1-100 parts of a silane coupling agent, and 1-100 parts of a double-bond silane coupling agent are uniformly mixed to obtain an organosilicon monomer mixed solution; 1-50 parts of an acid or base catalyst and 1-500 parts of water are uniformly mixed to obtain an acid or base catalyst solution; (2) By weight, 1-50 parts of emulsifier, 0-50 parts of co-emulsifier, 0-400 parts of water and 1%-100% of the acid or base catalyst prepared in step (1) are mechanically stirred and heated to 20°C-90°C, 1%-100% of the organosilicon monomer mixture prepared in step (1) and 0%-99% of the acid or base catalyst are added dropwise within 1 minute-360 minutes, the temperature is raised to 50°C-95°C, and the reaction is carried out for 5 minutes-240 minutes. The remaining organosilicon monomer mixture and acid or base catalyst are added dropwise within 0.5 hours-6 hours, the reaction is carried out at a constant temperature for 1 hour-6 hours, the temperature is lowered to 10-40°C, the pH is adjusted to 4-10, and the silicone rubber core emulsion is obtained by filtration; (3) By weight, 1-50 parts of double bond-containing monomer, 1-100 parts of hard monomer, 0.01-5 parts of emulsifier, and 3-100 parts of water are emulsified in a high shear emulsifier for 1 minute to 10 minutes to obtain a double bond-containing pre-emulsion; 1-25 parts of functional monomer, 1-50 parts of double bond-containing monomer, 1-100 parts of hard monomer, 0.01-5 parts of emulsifier, and 1-50 parts of water are emulsified in a high shear emulsifier for 1 min-10 min to obtain a functional monomer emulsion; 0-1 parts of buffer and 0-50 parts of water are stirred and dissolved to obtain a buffer solution; 0.01-5 parts of catalyst and 1-500 parts of water are stirred and dissolved to obtain a catalyst solution; (4) By weight, 100 parts of silicone rubber core emulsion, 0-5 parts of emulsifier, 0-50 parts of water and the buffer solution prepared in step (3) are stirred and heated to 40-90°C, 1%-60% of the double bond-containing pre-emulsion prepared in step (3) and 1%-100% of the catalyst solution are added dropwise within 1 min-30 min, the temperature is raised to 50-90°C, the reaction is carried out for 1 min-120 min, the remaining double bond-containing pre-emulsion and 1%-100% of the catalyst solution are added dropwise within 0.5 h-4 h, the temperature is raised to 60-95°C and the reaction is carried out for 0.5 h-6 h; (5) Cooling to 30-90°C, adding the functional monomer emulsion prepared in step (3) and the remaining catalyst solution dropwise within 1 min-120 min, heating to 50-95°C and reacting for 0.5 h-6 h to prepare a silicone rubber core-shell emulsion; (6) Add 20-400 parts of solvent by weight to the reaction kettle, start stirring at room temperature, and add 100 parts of silicone rubber core-shell emulsion dropwise within 1 minute to 60 minutes for extraction. Continue stirring for 1 minute to 30 minutes after the addition, and then let it stand for 0.5 hours to 24 hours to separate the layers. Remove the lower water layer to obtain the upper silicone rubber core-shell particle solvent dispersion; (7) 10-1000 parts by weight of the prepared silicone rubber core-shell particle solvent dispersion and 100 parts by weight of epoxy resin are added to a reaction kettle and stirred, and then the temperature is raised to 60-120°C, and the solvent is removed by vacuum distillation for 0.5h-5h to prepare a pre-dispersion of core-shell particle modified epoxy resin.
2. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: The organosilicon monomer in step (1) is one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, octaphenylcyclotetrasiloxane, methylphenylcyclosiloxane, tetravinyltetramethylcyclotetrasiloxane, and low molecular weight hydroxy silicone oil, or a combination thereof; The silane coupling agent in step (1) is one of methyltrimethoxysilane, methyltriethoxysilane, octyltriethoxysilane, phenyltrimethoxysilane, phenyltrimethoxysilane, tetraethyl silicate, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-mercaptopropyl-trimethoxysilane, or a combination thereof; The double bond-containing silane coupling agent in step (1) is one of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, and vinyl-tris(2-methoxyethoxy)silane, or a combination thereof; The acid catalyst in step (1) is one of benzenesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, formic acid, and perchloric acid, or a combination thereof; the base catalyst is one of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water, sodium oxide, potassium oxide, sodium methoxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide, and tetramethylammonium hydroxide, or a combination thereof.
3. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: The emulsifier in steps (2) to (4) is one of sodium lauryl sulfate, sodium cetyl sulfate, sodium docusate, sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate, dodecylbenzenesulfonic acid, sodium didodecylphenyl ether disulfonate, fatty acid polyoxyethylene phosphate, sodium rosinate, sodium cyclohexane, sodium ricinoleate, isomeric tridecyl alcohol ether, polyoxyethylene octylphenol ether-10, sorbitan monolaurate, sorbitan monopalmitate, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, and dodecyldimethylbenzylammonium chloride, or a combination thereof; The co-emulsifier in step (2) is one of n-butanol, n-pentanol, ethylene glycol, ethanol, propylene glycol, isopropyl alcohol, polyvinyl alcohol, polyethylene glycol, acetone, butanone, ethyl acetate, methyl acetate, glycerol, polyglycerol ester, sodium chloride, sodium sulfate, sodium bicarbonate, or a combination thereof.
4. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: In step (2), the pH is adjusted using an alkaline aqueous solution or an acidic aqueous solution, wherein the alkaline aqueous solution is one of ammonia water, sodium hydroxide aqueous solution, sodium bicarbonate aqueous solution, sodium formate aqueous solution, sodium acetate aqueous solution, ammonium acetate aqueous solution, disodium hydrogen phosphate aqueous solution, dipotassium hydrogen phosphate aqueous solution, sodium pyrophosphate aqueous solution, and sodium phosphate aqueous solution, or a combination thereof; the acidic aqueous solution is one of benzenesulfonic acid aqueous solution, p-toluenesulfonic acid aqueous solution, dodecylbenzenesulfonic acid aqueous solution, hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution, formic acid aqueous solution, and perchloric acid aqueous solution, or a combination thereof.
5. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: The double bond-containing monomer in step (3) is one of styrene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, acrylic acid, lauryl methacrylate, glycidyl methacrylate, allyl glycidyl ether, allylamine, 4-vinylaniline, 4-penten-1-amine, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 1-penten-3-ol, acrylic acid, methacrylic acid, methylenediamine, maleic acid, crotonic acid, allyl methacrylate, divinylbenzene, dicyclopentadiene acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, and ethoxypentaerythritol tetraacrylate, or a combination thereof; The hard monomer in step (3) is one of α-methylstyrene, N-vinylcarbazole, methacrylic acid, acrylamide, vinylnaphthalene, vinylimidazole, 3,4-ethylenedioxythiophene, maleimide, vinylbiphenyl, 4-vinylbenzoic acid, vinyltrimethoxysilane, and 2-vinylpyridine, or a combination thereof.
6. The pre-dispersion liquid of a core-shell particle modified epoxy resin and the preparation method thereof according to claim 1, characterized in that: The glass transition temperature of the ratio between the double bond pre-emulsion and the monomers in the functional monomer emulsion calculated by the FOX equation is higher than 105°C.
7. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: The functional monomer in step (3) is one of epoxy-containing functional monomers, amino-containing functional monomers, hydroxyl-containing functional monomers, and carboxyl-containing functional monomers, or a combination thereof.
8. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 7, characterized in that: The epoxy-containing functional monomer is one of glycidyl methacrylate and allyl glycidyl ether or a combination thereof; the amino-containing functional monomer is one of allylamine, 4-vinylaniline, and 4-pentene-1-amine or a combination thereof; the hydroxyl-containing functional monomer is one of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and 1-pentene-3-ol or a combination thereof; and the carboxyl-containing functional monomer is one of acrylic acid, methacrylic acid, methylenesuccinic acid, maleic acid, and crotonic acid or a combination thereof.
9. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: The buffering agent in step (3) is one of sodium bicarbonate, sodium formate, sodium acetate, ammonium acetate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium pyrophosphate, sodium phosphate, or a combination thereof; The catalyst in step (3) is one of diisopropylbenzene peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, azobisisobutylonitrile initiator, azobisisoheptylonitrile, or a combination thereof.
10. The method for preparing a pre-dispersion liquid of a core-shell particle modified epoxy resin according to claim 1, characterized in that: The solvent in step (6) is one of methyl formate, ethyl acetate, vinyl acetate, cyclohexanone, acetone, butanone, methyl isobutyl ketone, ethanol, isopropyl alcohol, triethylene glycol, propylene glycol, diethanolamine, triethanolamine, cyclohexane, n-hexane, n-heptane, xylene, toluene, dimethylformamide, acetonitrile, N-methylpyrrolidone, ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol butyl ether, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, chloroform, dichloroethane, and dichloromethane, or a combination thereof; the epoxy resin in step (7) is one of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, epoxidized olefin compound, heterocyclic and mixed epoxy resin, or a combination thereof.
Citation Information
Patent Citations
Preparation method of epoxy group-containing agglomerated siloxane-acrylate elastomer and application of epoxy group-containing agglomerated siloxane-acrylate elastomer in low-temperature toughened nylon tube
CN114478952A
Preparation method of nano silicone rubber core-shell structure polymer toughened epoxy resin
CN114685943A
Acrylate matte core-shell emulsion with excellent stain resistance and preparation method thereof
CN116396437A
Toughened epoxy resin composition
US20190040182A1
Epoxy resin composition
US20200157340A1